Avaliação de fatores preditivos de intubação orotraqueal difícil em obesos submetidos a anestesia geral - OLIVEIRA, Célia Regina Oliveira e (2017)
INTRODUCTION Obesity is a public health problem. There is a higher risk of anesthesia-related complications in obese. The aim of this study was to evaluate the predictive factors of difficult orotracheal intubation in obese patients undergoing general anesthesia. MATERIALS AND METHODS A prospective study in a tertiary public hospital through analysis of the American Society of Anesthesiologists, Mallampati and Cormack-Lehane scores, neck circumference, and thyromental distance and inter-incisor gap. Airway management material was used in several intubation attempts in 110 obese and 42 non-obese patients. Fisher’s exact test and Mann-Whitney test were performed for statistical analysis. RESULTS/DISCUSSION There was a difference when the number of intubation attempts was compared: the incidence was higher in obese patients. There was no difference regarding the use of airway management material. When comparing predictive factors of difficult airway with several intubation attempts and use of management material, difference was found only in the ASA score. The higher the ASA score in obese individuals, the more frequent the need for the use of management material. Most of the obese had an ASA score of III, as well as a thyromental distance shorter than five centimeters. Patients weighing more than 95 kg also had ASA III, Mallampati 3 and 4, larger neck circumference, and decreased thyromental distance. CONCLUSION Given the number of intubation attempts, the ASA classification was the only predictor of difficult intubation in obese patients. Mallampati scores 3 and 4, ASA III, larger neck circumference, and reduced thyromental distance were associated with obesity.